Exploring Pluralism in Oral Health Care: Dom Informal Dentists in Northern Lebanon. (28th January 2014) - Bochi, Giovanni
Abstract : This article describes a pluralistic regime of oral health provision in a rural part of northern Lebanon, where dental care came from two main sources: professionally trained dentists and "informal" Dom dentists with Syrian nationality. Relying on a combination of interviews and ethnography, I offer a multivocal view of oral health services that incorporates data from patients and formal and informal providers. I argue that informal dentistry constituted an interstitial and translocal mode of dental care. In the northern Lebanese Biqa Valley, close to the Syrian border, the local articulation of neoliberal health governance created opportunities for heterodox practices in oral health. The organization of informality was predicated on the presence of the open border between Syria and Lebanon, which favored patterns of flexible cross‐border mobility. In this context, informal dentistry was not alternative, but supplementary and lateral in relation to official forms of oral health provision.